The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.2166/wst.2006.617
|View full text |Cite
|
Sign up to set email alerts
|

Pollutant removal efficiency of alternative filtration media in stormwater treatment

Abstract: Sorption experiments were used to assess the ability of various materials (sand, compost, packing wood, ash, zeolite, recycled glass and Enviro-media) to remove heavy metal contaminants typically found in stormwater. Compost was found to have the best physicochemical properties for sorption of metal ions (Cu, Zn and Pb) compared with sand, packing wood, ash, zeolite and Enviro-media. The compost sorption of these metal ions conformed to the linear form of the Langmuir adsorption equation with the Langmuir cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 14 publications
1
28
0
Order By: Relevance
“…A wide variety of sorption media have been effective at reducing nutrient levels for stormwater, including recycled material mixtures ; mineral-based mixtures such as marble chips (Sengupta and Ergas, 2006) and oyster shells (Namasivayam et al, 2005), and organic materials such as leaf mulch (Ray et al, 2006), wood chips (Seelsaen et al, 2006) and alfalfa (Kim et al, 2000). Such media were selected for testing, which was composed of clay, sand, organic materials, or engineered compounds to remove more soluble reactive phosphorus (SRP) and total phosphorus (TP) Xuan et al, 2009a;Chang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…A wide variety of sorption media have been effective at reducing nutrient levels for stormwater, including recycled material mixtures ; mineral-based mixtures such as marble chips (Sengupta and Ergas, 2006) and oyster shells (Namasivayam et al, 2005), and organic materials such as leaf mulch (Ray et al, 2006), wood chips (Seelsaen et al, 2006) and alfalfa (Kim et al, 2000). Such media were selected for testing, which was composed of clay, sand, organic materials, or engineered compounds to remove more soluble reactive phosphorus (SRP) and total phosphorus (TP) Xuan et al, 2009a;Chang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…One gram of compost sourced from household and garden waste can remove 97.9% of lead, 97.7% of cadmium, 95.9% of zinc and 92.4% of copper from a 100 mg/L metal solution [8] while 6 g of mulch can remove more than 80% of copper and zinc [9]. It was also shown that the sorption capacity of compost sourced from kerbside (garden) waste was 11.2 mg/g at pH 5 [1]. Using municipal compost in combination with calcite to remediate acid mine drainage, the maximum sorption capacity of compost in a column was 3.9 mg/g at pH 6.5 [10].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that compost can reduce many water pollutants such as suspended solids, heavy metals, nitrogen, phosphorus, hydrocarbons, pesticides, petroleum products and other potentially hazardous substances [1][2][3]. Compost has been applied successfully as a best management practice in stormwater treatment systems such as compost blankets, compost filter berms and compost filter socks [4].…”
Section: Introductionmentioning
confidence: 99%
“…The road runoff contains a variety of vehicular pollutants at concentrations commonly above regulatory limits, including suspended solids, polycyclic aromatic hydrocarbons (PAHs), and an array of heavy metals [1][2][3][4][5][6][7][8]. Although the underlying geochemical mechanisms responsible for pollutant treatment have received attention by the scientific research community [3,5,6,[9][10][11], studies tend to be site-specific and yield wildly varying pollutant removal efficiency data. This is hardly surprising, as there is no data on how the biology or lithology of filter drains affects their performance, nor is there a solid benchmarked data-set of metal removal efficiencies from well-controlled laboratory experiments.…”
Section: Introductionmentioning
confidence: 99%